A filling body-surrounding rock combined structure damage monitoring and stability determination method based on multi-source information fusion
By integrating acoustic emission, full-field strain observation and microscopic characterization through a multi-source information fusion monitoring method, the monitoring and parameter optimization problems of nano-grouting materials in the reinforcement of fractured rocks were solved, and the accuracy of multi-scale damage characterization and stability determination was improved.
Patent Information
- Application Number
- CN202611261861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-06
AI Technical Summary
Existing technologies for reinforcing fractured rocks lack systematic research on nano-grouting materials, failing to fully reflect the damage state and stability of the filling-surrounding rock composite structure. Furthermore, existing monitoring methods are limited in scope and accuracy, and cannot provide parameter optimization supported by multi-source data.
A multi-source information fusion monitoring method is adopted, integrating acoustic emission, full-field strain observation, longitudinal wave velocity testing and micro-scale characterization modules. Combined with macro-fine-micro multi-scale analysis, damage monitoring and stability assessment of the filling body-surrounding rock composite structure are realized, and the optimal grouting parameters are determined through multi-dimensional parameter optimization.
This study achieved a comprehensive characterization of the multi-scale damage evolution process of the infill-surrounding rock composite structure, improved the accuracy and precision of stability assessment, provided theoretical support for the engineering application of nano-grouting materials, and optimized the design of grouting parameters.
Smart Images

Figure CN123045834A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of geotechnical engineering, underground engineering surrounding rock reinforcement and stability monitoring technology. Specifically, it relates to a method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion. It is applicable to multi-scale damage evolution monitoring, quantitative stability evaluation, and optimization of grouting reinforcement parameters after grouting reinforcement of fractured and weak surrounding rock in underground engineering such as water conveyance tunnels, mine roadways, and traffic tunnels. It is especially suitable for evaluating the grouting reinforcement effect of weak surrounding rock such as silty red sandstone that is prone to disintegration when exposed to water and is prone to large deformation and instability after excavation. Background Technology
[0002] The safety and stability of water conveyance tunnels in hydraulic dams are core prerequisites for promoting high-quality development of water conservancy projects and building a solid water security barrier. They are also a key foundation for ensuring the safe and stable operation of dams and preventing safety risks in water conservancy projects. Furthermore, they are crucial for achieving efficient water resource allocation and ensuring regional water supply and flood control security. During the construction of water conveyance tunnels, the surrounding rock is highly susceptible to large deformation, instability, and collapse after excavation and unloading under high ground stress. Research shows that tunnel deformation is mainly towards the tunnel's free face, starting approximately one tunnel diameter away from the tunnel face and ending more than two tunnel diameters away. Moreover, 75% of the deformation occurs after excavation. Red sandstone and mudstone are typical weak surrounding rocks. After excavation and unloading, they are prone to damage and fracture under the action of ground stress. If support measures are not taken in time, they are very likely to converge and deform into the excavation space, resulting in "large deformation of soft rock" disaster. This disaster is one of the geological disasters that causes the largest proportion of full-face hard rock tunnel boring machine (TBM) jamming, which has a serious adverse impact on the safe and efficient construction of the project.
[0003] Currently, protective measures for surrounding rock lining mainly include shotcrete and anchor support, grouting reinforcement, and surrounding rock mesh. However, for the soft rock fracture zones commonly found in water conveyance tunnels, shotcrete and anchor support and surrounding rock mesh have limited reinforcement effects. Grouting reinforcement, on the other hand, is currently recognized as the most effective method and is widely used in various underground engineering projects. Grouting reinforcement involves injecting a cementitious grout into the rock fractures and pores, achieving fracture filling, rock block cementation, and overall structural reconstruction. This significantly improves the integrity, strength, and deformation resistance of fractured surrounding rock, effectively suppressing large deformations, rockfalls, and collapses in soft rock, ensuring the continuity and safety of TBM tunneling. In actual engineering and laboratory tests, grouting process parameters directly determine the grout diffusion range, filling density, and rock-grout interface bonding strength. Among these, the water-cement ratio of the grouting material and the grouting pressure are the most critical control indicators, playing a decisive role in the reinforcement effect on fractured red sandstone.
[0004] The water-cement ratio of grouting materials directly affects the fluidity, stability, cementing properties, and later-stage strength of the grout, and is a key factor determining the injectability and reinforcement effect of the grout. When the water-cement ratio is too high, the grout viscosity is low and the fluidity is strong, making it easy to penetrate micro-cracks, but it is prone to bleeding, segregation, and shrinkage, leading to increased porosity and significantly reduced strength in the consolidated body, making it difficult to effectively cement fractured rock. When the water-cement ratio is too low, the grout viscosity increases significantly, weakening its flow and diffusion capacity, making it difficult to penetrate into the fine cracks of the rock mass. It is prone to accumulating near the grouting port, forming local blockages and grouting blind zones, resulting in problems such as incomplete filling and uneven reinforcement. A suitable water-cement ratio allows the grout to possess both good fluidity and cementing properties, enabling it to fully penetrate the fractured structural surfaces of red sandstone and form a dense consolidated body after hydration and hardening, significantly improving the peak strength, elastic modulus, and residual strength of the fractured sample.
[0005] Grouting pressure determines the driving and diffusion capacity of the grout, affecting its propulsion distance, filling degree, and compaction effect within the fracture network. When the grouting pressure is too low, the grout lacks sufficient power to penetrate small fractures within the rock mass, resulting in a limited diffusion range and inability to fully penetrate the fractured area. This can easily lead to unfilled cavities, resulting in noticeable weak points in the reinforced sample. Conversely, excessively high grouting pressure, while significantly increasing the diffusion range, can easily cause secondary splitting damage to the already fractured red sandstone, expanding existing fractures and even causing rock fragment displacement and structural loosening, thus reducing the overall stability of the surrounding rock. Furthermore, excessively high grouting pressure can also cause grout to flow along weak points in the surrounding rock, leading to material waste and reinforcement failure. A reasonable grouting pressure can, without causing new damage, drive the grout to fully fill the fracture space, expel fracture water and gas, improve the density and adhesion of the rock-grout interface, and transform the fractured sample from a loose state into a cohesive load-bearing structure, significantly enhancing its deformation resistance and load-bearing characteristics.
[0006] Currently, scholars both domestically and internationally have conducted extensive research on grouting reinforcement of fractured rocks, resulting in a series of findings on the influence and mechanism of different grouting materials, water-cement ratios, and grouting pressures on the recovery of the mechanical strength of grouted reinforced fractured rocks. However, existing research still has the following core shortcomings: First, existing research largely focuses on ordinary silicate cement grouting materials, while research on high-permeability nano-modified grouting materials is relatively scarce. Nano-grouting materials, with their ultra-fine particle size, high permeability, and excellent cementing properties, offer a new approach to reinforcing weak surrounding rocks. However, systematic research on the mechanical properties and damage evolution of fractured rocks using these materials is severely lacking. This research limitation seriously restricts the widespread application of nano-grouting materials in practical engineering and hinders the long-term development of grouting reinforcement technology.
[0007] Secondly, while there is a lot of research on the reinforcement of rocks with cement grouting materials under different grouting pressures and water-cement ratios, there is still insufficient research on the mechanical strength recovery, crack evolution, and surface non-uniform deformation of rocks reinforced with nano-grouting materials under different grouting conditions. This lack of research provides systematic theoretical support for the engineering parameter design of nano-grouting materials and limits their engineering application scope.
[0008] Third, although significant progress has been made in the study of the microscopic mechanism of cement grouting materials for rock reinforcement under different grouting water-cement ratios and grouting pressures, the pore structure and micromorphological characteristics of nano-grouting materials for rock reinforcement under different grouting conditions are still unclear, and the explanation of the relevant strength recovery mechanism is still lacking. It is impossible to reveal the reinforcement mechanism of nano-grouting materials from multiple scales from macro to micro.
[0009] Fourth, existing methods for judging the effectiveness of grouting reinforcement and the stability of surrounding rock mostly use a single uniaxial compressive strength index, without combining multi-source information such as acoustic emission damage characteristics, microscopic deformation characteristics, and microstructural characteristics. These methods cannot comprehensively reflect the true damage state and stability performance of the filling body-surrounding rock composite structure, resulting in insufficient judgment accuracy. Furthermore, they cannot systematically quantify the correlation mechanism between grouting parameters and the stability of the composite structure, making it difficult to guide the precise optimization of grouting parameters on-site.
[0010] Therefore, in view of the above-mentioned shortcomings of the existing technology, it is urgent to develop a method for damage monitoring and stability assessment of infill-surrounding rock composite structures based on multi-source information fusion, to achieve damage evolution characterization at multiple scales from macro to micro, to establish a quantitative stability evaluation system, and to systematically reveal the regulation mechanism of water-cement ratio and grouting pressure of nano-grouting materials on the strength recovery of fractured surrounding rock, so as to provide comprehensive theoretical and technical support for the engineering application of nano-grouting materials. Summary of the Invention
[0011] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for damage monitoring and stability assessment of infill-surrounding rock composite structures based on multi-source information fusion, thereby solving the following technical problems: To address the technical problem that existing monitoring methods are limited and cannot achieve multi-scale characterization of the damage evolution process of the infill-surrounding rock composite structure, and to overcome the shortcomings of single monitoring methods that can only reflect local features and cannot fully reveal the damage mechanism; To address the technical problem that existing stability assessments rely solely on a single strength index without incorporating multi-source damage characteristic parameters, resulting in insufficient accuracy and an inability to accurately reflect the stability state of composite structures, a quantitative, multi-dimensional stability evaluation system should be established. To address the technical issues of lacking systematic multi-source data support for parameter optimization of existing nano-grouting materials for reinforcing fractured surrounding rock, and the inability to clearly define the control mechanism of water-cement ratio and grouting pressure on the stability of composite structures, this study aims to provide precise guidance for the design of engineering grouting parameters. To address the technical problem that existing research cannot reveal the strength recovery mechanism of fractured surrounding rock reinforced by nano-grouting materials from multiple scales (macro-fine-micro), and to improve the theoretical system of nano-grouting material reinforcement.
[0012] To achieve the above objectives, the present invention provides the following technical solution: A method for damage monitoring and stability assessment of infill-surrounding rock composite structures based on multi-source information fusion includes the following steps: S1 Sample Preparation: Standard rock samples conforming to engineering rock mass testing standards were prepared from the target surrounding rock. Fractured surrounding rock samples with real through-cracks were prepared by uniaxial compression tests. The fractured surrounding rock samples were reinforced by high-pressure grouting with grouting material. The grouting was carried out in constant pressure mode. After reaching the preset pressure, the pressure was maintained for 120 minutes. After the pressure was maintained, the pressure was released in a stepwise manner by reducing the pressure by 0.5 MPa every 5 minutes. After the pressure was released, the samples were cured for 28 days to obtain the filling body-surrounding rock composite structure sample. Specifically, the target surrounding rock is red sandstone, a typical weak surrounding rock in water conveyance tunnels. The standard rock sample is a cylindrical standard specimen with a diameter of φ50mm×100mm, and the height and diameter errors do not exceed ±0.3mm. The uniaxial compression test adopts a displacement control mode with a loading rate of 0.03mm / min. The specimen is loaded until macroscopic through-cracks are generated, and then unloaded to obtain a fractured surrounding rock specimen. The grouting material includes high-permeability nano-grouting material and 42.5P·O type ordinary silicate cement grouting material. The high-permeability nano-grouting material has a maximum particle size of <10μm, a density of 3.77g / cm³, and a specific surface area of 421m² / kg. The ordinary silicate cement has a maximum particle size of 50μm, a density of 3.16g / cm³, and a specific surface area of 386m² / kg.
[0013] Furthermore, the grouting pressure of the high-pressure grouting is set in the range of 2MPa to 15MPa, and the water-cement ratio of the grouting material is set in the range of 0.5 to 0.9, covering the commonly used mix ratio range in engineering; the standard curing conditions are a temperature of 20℃ and a relative humidity of 90%RH, and the sample quality and longitudinal wave velocity are monitored regularly during the curing period.
[0014] The parameter range is based on the following: When the grouting pressure is below 2 MPa, the grout dynamics are insufficient, the crack filling rate is less than 60%, and the reinforcement effect is poor; when the grouting pressure is above 15 MPa, it will induce hydraulic fracturing effect, causing secondary damage to the fractured surrounding rock and reducing the overall stability. Therefore, the grouting pressure range is limited to 2 MPa~15 MPa. When the water-cement ratio is below 0.5, the grout viscosity is too high, the fluidity is insufficient, and it cannot penetrate into the micro-cracks of the rock mass, easily forming grouting blind zones; when the water-cement ratio is above 0.9, the grout bleeding rate exceeds 30%, the porosity increases significantly after consolidation, and the strength deteriorates significantly. Therefore, the water-cement ratio range is limited to 0.5~0.9.
[0015] S2 Multi-Source Monitoring System Construction: A multi-source information monitoring system integrating acoustic emission (AE) monitoring module, three-dimensional full-field strain observation module, longitudinal wave velocity testing module and microscopic characterization module was built. The system calibration and experimental parameter settings of each module were completed to realize synchronous acquisition and fusion analysis of multi-source data. Specifically, the acoustic emission monitoring module includes a multi-channel acoustic emission acquisition system, an acoustic emission sensor, and a preamplifier. The parameters are set as follows: signal trigger threshold 45dB, sampling frequency 1MHz, and preamplifier gain 40dB. Before the test, high-vacuum grease is used as a coupling agent to fix the acoustic emission sensor to the preset measurement point on the sample surface. The coupling effect and acquisition sensitivity of the system are verified by a standard lead breaking test (0.5mm lead core, extension length 2.5mm, breaking angle 30°). After the verification is qualified, the test is carried out.
[0016] The three-dimensional full-field strain observation module is a three-dimensional digital image correlation (3D-DIC) binocular vision measurement system. Before the test, the sample surface is treated with matte black and white spray paint to create a white background with black speckles, the speckle diameter of which is about 2 to 3 pixels. The measurement distance and camera spacing are determined according to the sample size, and the camera focal length and aperture are adjusted. The binocular system is calibrated using a 12×9 dot matrix standard calibration board. The calibration reprojection error is less than 0.02 pixels, and the mapping relationship between image pixels and actual physical size is established.
[0017] The longitudinal wave velocity testing module uses a non-metallic ultrasonic testing and analysis instrument. Before the test, the system is calibrated with zero delay to ensure that the transmitting and receiving transducers are tightly coupled to the sample end face, and the test error is controlled within 5%.
[0018] The microscopic characterization module includes a high-resolution X-ray three-dimensional micro-CT system for soil and rock and a scanning electron microscope (SEM), which are used for characterizing the three-dimensional pore and fracture structure inside the sample and observing the microscopic morphology of the magma-rock interface, respectively.
[0019] S3 Synchronous monitoring during loading: The infill-surrounding rock composite structure specimen was placed in a rock pressure testing machine and a uniaxial compression loading test was carried out. During the loading process, stress-strain data, acoustic emission signals, and three-dimensional full-field strain images were collected simultaneously. The longitudinal wave velocity of the specimen was tested before and after loading. After loading, the specimen was characterized by CT three-dimensional scanning and SEM scanning for microstructure. Specifically, the uniaxial compression loading test was conducted using a DDZ-1000 rock pressure testing machine with a maximum test force of 1000kN and a main machine stiffness of 11.5GN / m. Displacement-controlled loading was used with a loading rate of 0.03mm / min. Before the test, Vaseline was evenly applied to both ends of the specimen to eliminate end effects and ensure that the specimen axis coincided with the loading axis of the testing machine.
[0020] The longitudinal wave velocity tests were conducted before grouting, after curing, and after loading failure. The longitudinal wave velocity of the sample was calculated using the following formula: in, Let L be the longitudinal wave velocity, and L be the distance between the wave emission point and the receiving point. The time it takes for a longitudinal wave to travel through the rock. This ensures zero delay for the instrument system.
[0021] In the microstructure characterization, CT three-dimensional scanning fixes the sample on the stage, and after completing a 360° rotation scan, the three-dimensional volume data is reconstructed. Threshold segmentation is used to distinguish the three phases of rock matrix, pores and slurry, and the porosity, pore size distribution and fracture filling rate are quantitatively analyzed. SEM scanning is used to prepare 10mm×10mm×20mm samples. After hydration is stopped with anhydrous ethanol, the samples are vacuum dried at 60℃. After gold sputtering, the morphology of the slurry-rock cementation surface and the development characteristics of hydration products are observed.
[0022] S4 Multi-source Information Fusion Damage Evolution Analysis: Based on the collected multi-source monitoring data, a fusion analysis is carried out from macro-fine-micro multi-scale: based on acoustic emission data, the crack initiation and propagation law and cracking mode of the composite structure under pressure are analyzed; based on three-dimensional full-field strain data, the non-uniform deformation characteristics of the sample surface are analyzed; based on micro-fine characterization data, the internal pore structure of the sample and the bonding state of the magma-rock interface are analyzed, and the regulation mechanism of grouting parameters on the damage evolution of the composite structure is clarified. Specifically, the crack initiation and propagation law analysis includes: characterizing the severity of a single micro-fracture based on acoustic emission ring count, characterizing the damage accumulation process throughout the loading process based on cumulative ring count, and analyzing the stage characteristics of damage evolution under different grouting parameters; based on the acoustic emission RA value (ratio of rise time to amplitude) and average frequency AF (ratio of ring count to duration), using AF=100RA as the dividing line to distinguish tensile cracks and shear cracks, statistically analyzing the proportion of the two types of cracks at different loading stages, and revealing the evolution law of crack types and the mechanism of failure mode transformation; this dividing line is calibrated based on a large amount of acoustic emission test data of grouting reinforced red sandstone samples, and can accurately distinguish the characteristic differences between the two types of fracture signals.
[0023] The surface non-uniform deformation feature analysis includes: reconstructing the three-dimensional full-field strain field of the sample surface based on the image sequence acquired by the 3D-DIC system, analyzing the evolution law of the overall axial strain and radial strain of the sample during the pre-peak loading process, extracting the position and development process of the strain localization zone, comparing the strain difference inside and outside the localization zone, and quantifying the degree of non-uniform deformation of the sample under different grouting parameters.
[0024] The microstructure analysis includes: comparing the crack distribution and porosity changes of the samples before and after grouting based on CT three-dimensional scanning results to quantitatively evaluate the crack filling effect of the grout; and analyzing the type, development degree and bonding state of hydration products and grout-rock interface under different grouting parameters based on SEM scanning images to reveal the influence mechanism of grouting parameters on the reinforcement effect at the microscopic level.
[0025] S5 Composite Structure Stability Determination: The strength recovery coefficient of the composite structure is calculated based on the mechanical parameters obtained from the uniaxial compression test. Combined with parameters from three dimensions—acoustic emission damage characteristics, microscopic deformation localization characteristics, and microscopic filling rate characteristics—the stability of the filling body-surrounding rock composite structure is quantitatively determined. The optimal grouting reinforcement parameters for the target surrounding rock are determined through multiple sets of comparative tests.
[0026] Specifically, the strength recovery coefficient The formula used to quantify the degree of bearing capacity recovery of fractured surrounding rock after grouting reinforcement is as follows: in, The peak compressive strength of the intact surrounding rock. The residual strength of the fractured surrounding rock. This represents the peak compressive strength of the infill-surrounding rock composite structure specimen.
[0027] Stability quantification judgment rules: Stability: Strength recovery coefficient ≥ 0.05, cumulative ringing count of peak acoustic emission ≤ 8000 times, crack filling rate ≥ 85%, strain localization coefficient ≤ 1.5; Relatively stable: strength recovery coefficient 0.03~0.05, cumulative ring count of peak acoustic emission 8000~15000 times, crack filling rate 70%~85%, strain localization coefficient 1.5~2.5; Unstable: strength recovery coefficient < 0.03, cumulative ringing count of peak-front acoustic emission > 15,000 times, crack filling rate < 70%, strain localization coefficient > 2.5; By combining the parameters of the above four dimensions, the stability of the combined structure is quantitatively evaluated, and the grouting parameters corresponding to the peak value of the strength recovery coefficient and the optimal multi-dimensional damage characteristics are taken as the optimal grouting reinforcement parameters for the target surrounding rock.
[0028] The beneficial effects of this invention are as follows: 1. Addressing the limitations of existing single-scale monitoring techniques, this invention achieves multi-source information fusion monitoring across macroscopic, fine, and microscopic scales, comprehensively characterizing the damage evolution process of the infill-surrounding rock composite structure. This invention integrates four monitoring modules: acoustic emission, three-dimensional full-field strain observation, longitudinal wave velocity testing, and CT / SEM microscopic characterization. From three dimensions—macroscopic mechanical response, fine deformation evolution, and microstructural changes—it comprehensively reveals the entire process of crack initiation, propagation, and penetration during the compression process of the composite structure. This overcomes the shortcomings of traditional single-scale monitoring methods, which can only reflect local characteristics and cannot reveal the essential damage mechanism, significantly improving the comprehensiveness and accuracy of damage characterization.
[0029] 2. To address the shortcomings of insufficient accuracy in existing stability assessment technologies, a multi-dimensional quantitative stability assessment system has been established, significantly improving the accuracy of stability evaluation. This invention breaks through the traditional evaluation model that relies solely on a single peak strength, introducing a strength recovery coefficient to quantify the strength recovery effect. Combined with acoustic emission damage characteristics, microscopic deformation localization characteristics, and microscopic filling rate characteristics, the stability of the composite structure is comprehensively assessed from four dimensions: bearing capacity, internal damage, deformation uniformity, and microscopic density. The evaluation results are more closely aligned with engineering realities and can truly reflect the stability state of the surrounding rock after grouting reinforcement, significantly improving the accuracy compared to traditional single-indicator assessments.
[0030] 3. Addressing the lack of support for optimizing nano-grouting parameters in existing technologies, this invention systematically reveals the regulatory mechanism of grouting parameters on the stability of composite structures, achieving precise optimization of grouting parameters. Through multiple sets of comparative experiments, this invention clarifies the performance differences between nano-grouting materials and ordinary cement grouting materials: under the same water-cement ratio, the peak strength of samples reinforced with nano-grouting materials is 1.6 to 2.1 times that of cement materials, and the strength recovery coefficient can reach up to 2.08 times that of cement materials. The invention quantifies the influence of water-cement ratio and grouting pressure on the mechanical properties, damage evolution, and microstructure of composite structures, and determines the optimal parameter range for grouting reinforcement of weak red sandstone surrounding rock (water-cement ratio of nano-grouting material 0.6, grouting pressure 10 MPa), providing systematic and directly applicable theoretical and data support for on-site grouting design.
[0031] 4. Addressing the gap in existing research on the mechanism of nano-grouting reinforcement, this invention reveals the strength recovery mechanism of nano-grouting materials in reinforcing fractured surrounding rock at multiple scales, thus improving the theoretical system of grouting reinforcement. Combining macroscopic mechanical experiments, microscopic deformation monitoring, and microstructural characterization, this invention elucidates the principle by which nano-grouting materials achieve strength recovery through a three-level mechanism of "macroscopic crack cementation - microscopic pore filling - microscopic interface bonding." It also clarifies the synergistic control principle of "water-cement ratio balancing grout fluidity and consolidation strength, and grouting pressure balancing filling efficiency and secondary splitting damage," filling the gap in multi-scale mechanism research on nano-grouting materials for reinforcing fractured surrounding rock.
[0032] 5. The method and process are standardized, highly operable, and widely applicable in engineering. The test process, monitoring methods, and judgment rules of this invention have all formed a standardized system. It is not only applicable to weak surrounding rocks such as red sandstone, but can also be extended to evaluate the grouting reinforcement effect of various fractured surrounding rocks such as mudstone and limestone. It can directly serve the surrounding rock reinforcement design and stability evaluation of various underground projects such as water conveyance tunnels, mine roadways, and traffic tunnels, and has extremely high engineering application value. Attached Figure Description
[0033] Figure 1 Overall technical roadmap of the method of this invention; Figure 2 Uniaxial compressive stress-strain curves of infill-surrounding rock composite structure specimens under different water-cement ratios; Figure 3 Comparison of the effects of grouting parameters on the strength and strength recovery coefficient of the composite structure; Figure 4 Evolution curves of acoustic emission ring count and cumulative ring count of combined structures under different grouting parameters; Figure 5 Acoustic emission RA-AF distribution and crack type ratio of composite structure specimens; Figure 6 CT three-dimensional reconstruction of pore structure of grouting reinforced specimen; Figure 7 SEM microstructure of the grouting reinforced specimen. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] It should be noted that the technical means not described in detail in the following embodiments are all conventional means in the field, are not the key points of the invention, and will not be elaborated upon.
[0036] like Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, this embodiment takes a typical silty red sandstone from a water conveyance tunnel project in southwestern my country as the research object, and conducts damage monitoring and stability assessment of the infill-surrounding rock composite structure according to the method of this invention. The specific implementation process is as follows: Example 1: Experimental Materials and Construction of a Multi-Source Monitoring System 1.1 Preparation of experimental materials (1) Preparation of surrounding rock samples Homogeneous red sandstone blocks obtained from core sampling at the engineering site were selected and processed into cylindrical standard rock samples of φ50mm×100mm according to the "Standard for Engineering Rock Mass Testing Methods". Samples with diameter and height deviations not exceeding ±0.3mm were selected. The initial basic parameters of all samples were tested, including diameter, height, mass, and initial P-wave velocity. Finally, 30 sets of samples with basic parameter deviations of less than 5% were selected as test objects. The average parameters of the samples were: diameter 49.94mm, height 100.04mm, mass 438.51g, and initial P-wave velocity 2.408km / s.
[0037] XRD phase analysis determined the mineral composition of the red sandstone to be 87% silica (SiO2), 5% grossular, and 8% albite, which is consistent with the mineral composition characteristics of typical sedimentary red sandstone.
[0038] Uniaxial compression fracture tests were conducted on standard rock samples using a DDZ-1000 rock pressure testing machine. The loading rate was 0.03 mm / min. The load was applied until a macroscopic through-crack appeared in the sample, and then the load was immediately unloaded to obtain fractured red sandstone samples. The basic parameters of the fractured samples were tested as follows: average crack height 99.04 mm, average crack mass 435.8 g, average longitudinal wave velocity after cracking 1.436 km / s, and average residual strength 0.79 MPa. The average peak compressive strength of the intact red sandstone samples was 39.5 MPa.
[0039] (2) Preparation of grouting materials This embodiment uses two grouting materials for comparative testing: ① High-permeability nano-grouting material: A new type of grouting material developed by China Coal Technology & Engineering Mining Research Institute. Its physical parameters are: maximum particle size <10μm, density 3.77g / cm³, specific surface area 421m² / kg, maximum reaction temperature <25℃. The main mineral components are calcium magnesium silicate and magnesite. It has the characteristics of high permeability, micro-expansion and dense solidified body. ② Ordinary Portland cement grouting material: 42.5P・O type ordinary Portland cement, with physical parameters as follows: maximum particle size 50μm, density 3.16g / cm³, specific surface area 386m² / kg, and maximum reaction temperature 69℃, serving as a control group for commonly used engineering materials.
[0040] Two types of grouting materials were prepared with water-cement ratios of 0.5, 0.6, 0.7, 0.8, and 0.9 respectively. The grouting was carried out using a cement paste mixer with the following mixing regime: slow mixing for 120 seconds, pause for 15 seconds, and fast mixing for 120 seconds. Grouting tests were carried out immediately after the mixing was completed.
[0041] 1.2 High-pressure grouting test and specimen curing Grouting tests were conducted using a self-developed high-pressure grouting device. The device parameters were: grouting pressure range of 0~20MPa, grouting capacity of 3L, and oil delivery rate range of 0~15mL / min. It has two grouting modes: constant pressure and pressurization. In this embodiment, the constant pressure grouting mode was adopted.
[0042] Grouting test operation procedure: ① Remove the plastic wrap from the surface of the cracked red sandstone, clean the surface debris, use 3-5 rubber bands to fix the cracked rock block to prevent the rock block from falling, and put the sample into a special steel cup; ② Place the steel cup into the groove of the grouting container, pour in the prepared grouting slurry until the slurry overflows the top of the sample, and tighten the bolts on the top cover of the grouting container; ③ Open the vent and the filling funnel, add slurry until slurry flows out continuously from the vent. After confirming that there is no residual air in the container, close the vent and the filling funnel. ④ Operate the control panel, set the oil delivery rate to 10mL / min to increase the pressure, and switch to the pressure holding mode after reaching the preset pressure, and hold the pressure for 120min; ⑤ After the pressure holding is completed, the pressure is released in stages, with the pressure reduced by 0.5 MPa every 5 minutes until the pressure drops to 0. The sample is then removed, excess grout is cleaned from the surface, and the initial mass and longitudinal wave velocity after grouting are tested. The staged pressure release can avoid the problems of grout back seepage and secondary opening of cracks caused by direct pressure release, and improve the density of grout filling.
[0043] ⑥ Place the sample in a standard constant temperature and humidity curing chamber at 20℃ and 90%RH for 28 days, and monitor the changes in sample mass and longitudinal wave velocity daily.
[0044] This embodiment sets up two sets of comparative experiments: Group 1: Water-cement ratio variable test. The grouting pressure was fixed at 10 MPa, and the water-cement ratios were 0.5, 0.6, 0.7, 0.8, and 0.9, respectively. Three groups of samples were prepared for reinforcement with nano-grouting material and cement grouting material, respectively. Group 2: Variable grouting pressure test. Nano-grouting material was used, with a water-cement ratio fixed at 0.6. Grouting pressures were 2MPa, 5MPa, 8MPa, 10MPa, 12MPa and 15MPa, and 3 groups of reinforced samples were prepared under each pressure.
[0045] 1.3 Construction and Calibration of Multi-Source Monitoring System A multi-source monitoring system was constructed according to the method of this invention, and the parameter settings and calibrations of each module are as follows: (1) Acoustic emission monitoring module: An 8-channel acoustic emission acquisition system is adopted, with a trigger threshold of 45dB, a sampling frequency of 1MHz, and a preamplifier gain of 40dB. Two acoustic emission sensors are symmetrically arranged on the sample surface. High vacuum grease is applied to the bottom surface of the sensors as a coupling agent, and they are fixed with insulating tape. The standard lead breakage test is used to verify that the sensor response sensitivity is consistent and the coupling effect is qualified.
[0046] (2) 3D-DIC three-dimensional full-field strain observation module: a binocular industrial camera system with a resolution of 2448×2048 and a frame rate of 15fps is used; a matte white paint is sprayed on the observation surface of the sample as a base color, and after drying, black speckle is sprayed evenly with a speckle diameter of about 2~3 pixels; a 12×9 dot matrix calibration plate is used to complete the calibration of the binocular system, and the calibration reprojection error is less than 0.02 pixels to ensure measurement accuracy.
[0047] (3) Longitudinal wave velocity test module: A non-metallic ultrasonic testing and analysis instrument with a frequency of 50kHz is used. First, the system is tested with zero delay. The test is repeated 3 times and the average value is taken. During the test, Vaseline is applied to the end face of the sample and the surface of the transducer to ensure tight coupling. Each sample is tested 3 times and the average value is taken. The error is controlled within 5%.
[0048] (4) Microscopic characterization module: A high-resolution X-ray three-dimensional micro-CT system was used to perform CT three-dimensional scanning with a spatial resolution of 5 μm, a scanning voltage of 160 kV, and a current of 150 μA; a Sigma300 scanning electron microscope was used to perform SEM scanning with an accelerating voltage of 15 kV and a magnification of 500 to 5000 times.
[0049] Example 2: Test on the working performance of grouting materials and the mechanical properties of the foundation 2.1 Performance Testing of Grouting Materials The fluidity, bleeding rate, and setting time of two grouting materials under different water-cement ratios were tested according to standard methods. The test results are as follows: (1) Flowability test results As the water-cement ratio increased from 0.5 to 0.9, the fluidity of both grouting materials continued to rise: the fluidity of the nano-grouting material increased from 265 mm to 378.5 mm, while the fluidity of the cement grouting material increased from 220 mm to 376 mm. In the water-cement ratio range of 0.5–0.7, the fluidity of the nano-grouting material was significantly higher than that of the cement grouting material. For example, at a water-cement ratio of 0.6, the fluidity of the nano-grouting material was 310 mm, while that of the cement grouting material was only 268 mm, demonstrating the superior fluidity of the nanomaterial. In the water-cement ratio range of 0.7–0.9, the difference in fluidity between the two gradually narrowed, and the improvement in fluidity at higher water-cement ratios showed a marginal effect.
[0050] (2) Results of tests on water exudation rate and stone rate As the water-cement ratio increases, the bleeding rate of both grouting materials continues to rise, while the stone formation rate continues to decrease. The stone formation rate shows a significant linear negative correlation with the water-cement ratio. The bleeding rate of the nano-grouting material increased from 3.59% with a water-cement ratio of 0.5 to 35.8% with a water-cement ratio of 0.9. The fitting formula for the stone formation rate is y=-83.87x+139.13, and the coefficient of determination R²=0.99. The bleeding rate of cement grouting material increased from 6.40% with a water-cement ratio of 0.5 to 22.3% with a water-cement ratio of 0.9. The fitting formula for the stone rate is y=-38.51x+111.21, and the coefficient of determination R²=0.936.
[0051] In the water-cement ratio range of 0.5 to 0.6, the bleeding rate of nano-grouting materials is significantly lower than that of cement grouting materials, demonstrating the advantage of nanoparticles' high specific surface area in adsorbing free water. When the water-cement ratio exceeds 0.7, the bleeding rate of nano-grouting materials increases at a higher rate than that of cement materials, indicating that free water exceeds the adsorption limit of nanoparticles at high water-cement ratios, thus increasing the risk of bleeding.
[0052] (3) Results of setting time test As the water-cement ratio increases, the initial and final setting times of both grouting materials continue to lengthen: The initial setting time of the nano-grouting material increased from 585 min with a water-cement ratio of 0.5 to 930 min with a water-cement ratio of 0.9, and the final setting time increased from 965 min to 1260 min. The initial setting time of cement grouting material increased from 290 min for a water-cement ratio of 0.5 to 510 min for a water-cement ratio of 0.9, and the final setting time increased from 325 min to 580 min.
[0053] At the same water-cement ratio, the setting time of nano-grouting materials is significantly longer than that of cement materials. This is because the nanoparticles have high dispersibility, which hinders the formation of early flocculent cementitious structures. The longer setting time is conducive to the full diffusion and filling of the grout in the cracks.
[0054] 2.2 Mechanical property testing of grouting material (neat grout) Uniaxial compression tests were conducted on samples of two types of grouting materials with different water-cement ratios to test their mechanical properties. The results are as follows: (1) Stress-strain characteristics The stress-strain curves of both types of grouting materials were divided into compaction stage, elastic stage, yielding stage, and post-peak failure stage. With increasing water-cement ratio, the slope of the elastic stage gradually decreased, the peak strength continued to decrease, and the post-peak failure transitioned from brittle to ductile. At a water-cement ratio of 0.5, the nano-grouting material grout exhibited significant brittle failure characteristics, with a sharp drop in post-peak stress; at a water-cement ratio of 0.9, the post-peak failure showed a gentle plastic failure characteristic.
[0055] (2) Peak strength and residual strength The peak strength of the nano-grout decreased from 47.5 MPa at a water-cement ratio of 0.5 to 9.8 MPa at a water-cement ratio of 0.9, while that of the cement grout decreased from 30.5 MPa to 11.5 MPa. In the water-cement ratio range of 0.5 to 0.8, the peak strength of the nano-grout was significantly higher than that of the cement material, with a strength difference of 17 MPa at a water-cement ratio of 0.5, demonstrating the excellent bonding performance of the nanomaterial. At a water-cement ratio of 0.9, the strength of the nanomaterial was lower than that of the cement material, indicating that the strength degradation of the nanomaterial was more significant at high water-cement ratios.
[0056] The residual strength of both materials in the grout first increased and then decreased with the increase of water-cement ratio. The residual strength of the nano-grouting material reached a peak of 8.8 MPa at a water-cement ratio of 0.6, while that of the cement material reached a peak of 4.6 MPa at a water-cement ratio of 0.8. The residual strength of the nano-material was significantly higher than that of the cement material overall.
[0057] (3) Destruction Mode The failure mode of the nano-grouting material paste is mainly tensile failure. At a water-cement ratio of 0.5, multiple longitudinal tensile cracks appear on the sample surface, accompanied by a large amount of particle spalling, showing significant brittle characteristics. As the water-cement ratio increases, the number of cracks decreases, and the degree of spalling decreases. The failure mode of the cement grouting material paste gradually changes from shear failure at a water-cement ratio of 0.5 to tensile failure. At a water-cement ratio of 0.5, obvious oblique shear main cracks appear, while at high water-cement ratios, longitudinal tensile cracks dominate, accompanied by flaky spalling.
[0058] Example 3 Mechanical properties and damage evolution tests of composite structures under different water-cement ratios In this embodiment, the grouting pressure was fixed at 10 MPa, and the mechanical properties and damage evolution of the reinforced combination structure of nano-cement grouting materials under different water-cement ratios were tested.
[0059] 3.1 Macroscopic Mechanical Properties Analysis (1) Characteristics of stress-strain curves The stress-strain curves of the combined structures reinforced by the two materials are divided into four stages: compaction closure, elastic deformation, plastic deformation, and post-peak failure. The compaction stage of the sample with a water-cement ratio of 0.5 lasted the longest, indicating that the internal cracks were not fully filled and there were many pores. The compaction stage of the sample with a water-cement ratio of 0.6 to 0.7 was the shortest, while the elastic stage was the longest, indicating that the cracks were filled tightly and the overall integrity was good. The plastic stage of the sample with a water-cement ratio of 0.8 to 0.9 was prolonged, and the load-bearing capacity after the peak was more stable.
[0060] The peak stress of the nano-grouting material reinforced specimens was significantly higher than that of cement materials, and the post-peak load-bearing capacity was more stable, demonstrating a superior reinforcement effect.
[0061] (2) Comparison of mechanical parameters ① Peak Strength: The peak strength of the nano-grouting material-reinforced samples initially increased and then decreased with increasing water-cement ratio, reaching a peak of 3.34 MPa at a water-cement ratio of 0.6, 3.05 MPa at 0.7, and rebounding to 1.91 MPa at 0.9. In contrast, the peak strength of cement-reinforced samples continuously decreased with increasing water-cement ratio, reaching a peak of 1.99 MPa at a water-cement ratio of 0.5, and only 0.87 MPa at 0.9. At the same water-cement ratio, the peak strength of the nano-material-reinforced samples was on average 1.6 to 2.1 times that of the cement-reinforced samples.
[0062] ② Residual strength: The residual strength of the nano-grouting material reinforced specimens first increased and then decreased with the increase of water-cement ratio, reaching a peak of 0.66 MPa at a water-cement ratio of 0.7; the residual strength of the cement material reinforced specimens reached a peak of 0.46 MPa at a water-cement ratio of 0.7. The average residual strength of the nano-material was 1.3 to 1.8 times that of the cement material.
[0063] ③ Elastic modulus: The elastic modulus of the nano-grouting material reinforced sample reached a peak of 548 MPa at a water-cement ratio of 0.7, while that of the cement material reached a peak of 445 MPa at a water-cement ratio of 0.7. The overall stiffness of the nano-material was significantly higher than that of the cement material.
[0064] ④ Peak strain: When the water-cement ratio is 0.5, the peak axial and radial strains of both materials are the largest, indicating that the samples have more internal pores and larger compaction deformation at low water-cement ratios; when the water-cement ratio is 0.6~0.7, the peak strain is the smallest, the samples have high stiffness and small deformation, and the bearing capacity is optimal.
[0065] (3) Strength recovery coefficient Calculate the strength recovery coefficient using the formula: The strength recovery coefficient of the nano-grouting material reinforced specimen first increases and then decreases with the increase of water-cement ratio. It reaches a peak of 0.0638 when the water-cement ratio is 0.6, 0.0563 when the water-cement ratio is 0.7, decreases to 0.0145 when the water-cement ratio is 0.8, and rises back to 0.0287 when the water-cement ratio is 0.9. The strength recovery coefficient of the cement grouting material reinforced specimens continued to decrease with the increase of water-cement ratio, and was 0.0307 when the water-cement ratio was 0.5, and only 0.0021 when the water-cement ratio was 0.9. The results show that the strength recovery effect of nano-grouting materials is far superior to that of ordinary cement materials, and the optimal mixing ratio of nano-materials is 0.6~0.7.
[0066] 3.2 Damage Evolution Analysis Based on Acoustic Emission (1) Ring count and cumulative ring count The peak ring count of the nano-grouting material-reinforced specimens decreased continuously with increasing water-cement ratio. The peak ring count was 1985 at a water-cement ratio of 0.5, and dropped to 403 at a water-cement ratio of 0.9, indicating that the increase in water-cement ratio led to a decrease in the bonding strength of the grout and a weakening of the fracture energy release intensity. The cumulative ring count first decreased and then increased with increasing water-cement ratio, and was lowest at a water-cement ratio of 0.6, indicating that the specimen had the fewest micro-cracks and the best integrity at this ratio. The cumulative ring count was highest at a water-cement ratio of 0.8, indicating that micro-cracks continued to occur and the damage evolution was more gradual.
[0067] The peak ring count of the cement grouting material reinforced specimens was lower than that of the nanomaterials, and the cumulative ring count was also significantly lower than that of the nanomaterials. This indicates that the cement material reinforced specimens have fewer internal bonding points and fewer micro-crack events, resulting in a poor reinforcement effect.
[0068] (2) Cracking mode analysis Based on the RA-AF method for distinguishing crack types, the results show that: In the nano-grouting material reinforced samples, as the water-cement ratio increases, the proportion of tensile cracks gradually decreases while the proportion of shear cracks gradually increases: when the water-cement ratio is 0.5, the proportion of tensile cracks is 58.27% and that of shear cracks is 38.94%; when the water-cement ratio is 0.6, the proportion of tensile cracks is 51.86% and that of shear cracks is 44.86%; when the water-cement ratio is 0.7, the proportion of tensile cracks is 46.75% and that of shear cracks is 50.43%; after the water-cement ratio exceeds 0.7, the proportion of shear cracks exceeds that of tensile cracks, and the failure mode changes from tensile-dominated to shear-dominated.
[0069] The tensile crack ratio of cement grouting reinforced specimens was consistently above 61%, and the failure mode was consistently tensile failure, indicating that the bond strength between cement and rock was low, and the failure mainly occurred at the grout-rock interface due to tensile cracking.
[0070] 3.3 Non-uniform deformation analysis based on 3D-DIC Based on 3D-DIC full-field strain data, the deformation characteristics of the specimen surface were analyzed: The strain localization before the peak appeared earliest in the sample with a water-cement ratio of 0.5, and the strain concentration in the localized zone was the highest, indicating that the internal weak surface was obvious and the deformation was highly uneven. The samples with a water-cement ratio of 0.6 to 0.7 exhibited uniform axial and radial deformation before the peak, and the strain localization zone appeared latest with the lowest degree of localization, indicating that the samples had good overall integrity and strong deformation coordination ability. The degree of strain localization and deformation non-uniformity gradually increased in samples with a water-cement ratio of 0.8 to 0.9.
[0071] At the same water-cement ratio, the overall deformation of the sample reinforced with nano-grouting material is more uniform, and the degree of strain localization is significantly lower than that of cement material, indicating that the sample reinforced with nano-material has better overall integrity and stronger resistance to deformation.
[0072] Example 4: Mechanical properties and damage evolution of composite structures under different grouting pressures In this embodiment, a nano-grouting material was used with a fixed water-cement ratio of 0.6 to test the mechanical properties and damage evolution of the combined structure under different grouting pressures.
[0073] 4.1 Macroscopic Mechanical Properties Analysis (1) Peak strength and strength recovery coefficient As the grouting pressure increased from 2 MPa to 15 MPa, the peak strength and strength recovery coefficient of the composite structure both showed a trend of first increasing and then decreasing: At a grouting pressure of 2 MPa, the peak strength is 1.87 MPa and the strength recovery coefficient is 0.0275. When the grouting pressure is 10 MPa, the peak strength reaches a maximum of 3.34 MPa, and the strength recovery coefficient reaches a peak of 0.0638. After the grouting pressure exceeds 10 MPa, the peak strength and strength recovery coefficient continue to decrease. At 15 MPa, the peak strength drops to 2.12 MPa and the strength recovery coefficient is 0.0339.
[0074] The reason is that when the grouting pressure is below 10MPa, the increased pressure enhances the diffusion and filling capacity of the grout, resulting in a denser filling of the cracks. When the grouting pressure exceeds 10MPa, the high pressure induces a hydraulic fracturing effect, causing the original cracks to expand and resulting in secondary damage, which in turn reduces the reinforcement effect.
[0075] (2) Deformation characteristics When the grouting pressure is 2~8MPa, the compaction stage of the sample is relatively long, indicating that the grout filling is insufficient under low pressure and there are many internal pores. When the grouting pressure is 10MPa, the compaction stage is the shortest and the elastic stage is the longest, indicating that the sample stiffness is the greatest. When the grouting pressure is 12~15MPa, the compaction stage is extended again, indicating that high-pressure fracturing has generated new cracks and the internal pores of the sample have increased.
[0076] 4.2 Damage Evolution and Failure Characteristics (1) Acoustic emission characteristics When the grouting pressure is 10 MPa, the peak acoustic emission ring count of the sample is the lowest, and the cumulative ring count is the lowest, indicating that the internal damage before the peak is the least and the sample integrity is the best. When the grouting pressure is below 8 MPa, the peak ring count is high, indicating that there are many internal cracks and micro-fractures continue to occur. When the grouting pressure exceeds 10 MPa, the peak ring count increases again, indicating that secondary splitting has caused new damage and increased internal defects.
[0077] (2) Destruction Mode When the grouting pressure is 2~8MPa, the failure of the sample is mainly tensile failure, and the main crack develops along the original crack. When the grouting pressure is 10MPa, the failure mode is a mixed tensile-shear failure, the cracks are evenly distributed, there is no obvious through main crack, and the reinforcement effect is the best. When the grouting pressure is 12~15MPa, multiple secondary cracks appear, and the failure is accompanied by the spalling of a large number of rock blocks, indicating that high pressure fracturing leads to the overall deterioration of the sample.
[0078] Example 5: Analysis of the Microstructure and Strength Recovery Mechanism of Composite Structures 5.1 Pore Structure Analysis from CT Three-Dimensional Scans The internal pore structure of the sample was reconstructed by CT three-dimensional scanning, and the influence of grouting parameters on the filling effect was quantitatively analyzed. The porosity of the nano-grouting material reinforced with a water-cement ratio of 0.6 and a grouting pressure of 10 MPa decreased from 21.3% in the fractured sample to 7.8%, and the crack filling rate reached 89.2%. The large-diameter pores were basically filled by the grout, and the pore size distribution was mainly small-diameter, resulting in high overall density of the sample. When the water-cement ratio is 0.5, the slurry has poor fluidity and the microcrack filling rate is only 62.7%, with a large number of unfilled micropores. When the water-cement ratio is 0.9, bleeding causes the porosity to increase to 13.5% after consolidation, resulting in a deterioration in the filling effect. When the grouting pressure is 2 MPa, the crack filling rate is only 58.3%, and there are a large number of unfilled voids; when the grouting pressure is 15 MPa, high-pressure fracturing causes new cracks to be generated, the porosity rises back to 12.7%, and the filling effect deteriorates.
[0079] 5.2 SEM Scanning Microscopic Morphology Analysis Microscopic morphology of the magma-rock interface was observed using SEM: Under optimal parameters (water-cement ratio 0.6, grouting pressure 10MPa), the hydration products of the nano-grouting material are dense, generating a large amount of CSH gel, which is tightly bonded to the red sandstone matrix. There are no obvious gaps at the grout-rock interface, and the bonding strength is high. When the water-cement ratio is too high or too low, the hydration products are not fully developed, there are obvious gaps at the magma-rock interface, and the bonding strength is low. The hydration products of cement grouting materials have many pores, and there is a clear transition zone at the grout-rock interface, resulting in a significantly lower bonding strength than that of nanomaterials.
[0080] 5.3 Strength Recovery Mechanism The strength recovery mechanism of nano-grouting materials for reinforcing fractured red sandstone can be summarized in three aspects: At the macro level: the nano-slurry fully fills the macroscopic fissures of the fractured rock blocks through its high permeability, cementing the loose rock blocks into a whole, restoring the continuity of the rock mass, and improving the overall bearing capacity; At a microscopic level: the nano-slurry penetrates into the micropores and micro-fractures inside the rock, optimizes the pore structure of the rock mass, reduces porosity, reduces internal weak surfaces, enhances the deformation resistance of the rock mass, and inhibits the localization of strain. At the microscopic level: the hydration of nanoparticles generates dense cementitious products, forming a tight bonding interface with the rock matrix. Stress is transferred through interfacial adhesion, achieving stress coordination between rock blocks and improving the overall strength and stability of the composite structure.
[0081] The synergistic control mechanism of grouting parameters is as follows: a reasonable water-cement ratio is the core of balancing grout fluidity and consolidation strength. An appropriate water-cement ratio allows the grout to have sufficient fluidity to penetrate microcracks and form a high-strength solidified body after hydration. A reasonable grouting pressure is the core of balancing filling efficiency and secondary damage. Appropriate pressure promotes the grout to fully fill the cracks while avoiding high pressure-induced hydraulic fracturing that causes new damage.
[0082] Example 6: Stability Determination of Combined Structures and Determination of Optimal Grouting Parameters According to the stability quantification judgment rule of the present invention, the stability of the combined structure under different grouting parameters is quantitatively judged by comprehensively considering four dimensions: strength recovery coefficient, acoustic emission damage characteristics, 3D-DIC deformation characteristics, and micro-filling rate. The nano-grouting material reinforced the sample with a water-cement ratio of 0.6 and a grouting pressure of 10MPa showed the following characteristics: strength recovery coefficient ≥0.05 (0.0638), cumulative pre-peak ring count ≤8000 (6200-8000), crack filling rate ≥85% (89.2%), and strain localization coefficient ≤1.5 (1.32). The sample was deemed stable, with the best performance across all indicators, and the combined structure exhibited the best stability. The nano-grouting material reinforced sample with a water-cement ratio of 0.7 and a grouting pressure of 10 MPa had a strength recovery coefficient of 0.0563 ≥ 0.05, and all other indicators met the stability requirements. Its stability was second only to the optimal group, and it can be used as an alternative parameter. All indicators of the ordinary cement grouting material reinforced samples were in the relatively stable or unstable range, and the overall stability was poor. When the grouting pressure exceeds 10 MPa, hydraulic fracturing causes various indicators to deteriorate, and the stability drops to relatively stable or unstable. When the grouting pressure is below 8 MPa, insufficient filling leads to poor stability.
[0083] The optimal parameters for grouting reinforcement of weak red sandstone surrounding rock were finally determined to be: using high-permeability nano-grouting material, water-cement ratio of 0.6, and grouting pressure of 10 MPa. Under these parameters, the stability of the filling body-surrounding rock composite structure is the best, and the reinforcement effect is the best.
[0084] The above embodiments fully verify the feasibility and effectiveness of the method of the present invention, which can realize multi-scale damage monitoring and accurate stability determination of the filling body-surrounding rock composite structure, and provide reliable technical support for the design of engineering grouting reinforcement parameters.
Claims
1. A method for damage monitoring and stability assessment of infill-surrounding rock composite structures based on multi-source information fusion, characterized in that, Includes the following steps: S1 Sample Preparation: Standard rock samples conforming to engineering rock mass testing standards were prepared from the target surrounding rock. Fractured surrounding rock samples with real through-cracks were prepared by uniaxial compression tests. The fractured surrounding rock samples were reinforced by high-pressure grouting with grouting material. The grouting was carried out in constant pressure mode. After reaching the preset pressure, the pressure was maintained for 120 minutes. After the pressure was maintained, the pressure was released in a stepwise manner by reducing the pressure by 0.5 MPa every 5 minutes. After the pressure was released, the samples were cured for 28 days to obtain the filling body-surrounding rock composite structure sample. S2 Multi-Source Monitoring System Construction: A multi-source information monitoring system integrating acoustic emission monitoring module, three-dimensional full-field strain observation module, longitudinal wave velocity testing module and microscopic characterization module was built. The system calibration and parameter setting of each module were completed to achieve synchronous acquisition of multi-source data. S3 Simultaneous monitoring of loading process: uniaxial monitoring of the filling-surrounding rock composite structure sample. Compression loading test, stress-strain data and acoustic emission signals were collected simultaneously during the loading process. Three-dimensional full-field strain image; longitudinal wave velocity of the sample was tested before and after loading, and microstructure characterization of the sample was performed by CT three-dimensional scanning and SEM scanning after loading. S4 Multi-source Information Fusion Damage Evolution Analysis: Based on the collected multi-source data, a fusion analysis is carried out from macro-fine-micro multi-scale: based on acoustic emission data, the crack initiation and propagation law and cracking mode of the composite structure under pressure are analyzed; based on three-dimensional full-field strain data, the non-uniform deformation characteristics of the sample surface are analyzed; based on micro-fine characterization data, the internal pore structure of the sample and the bonding state of the magma-rock interface are analyzed, and the regulation mechanism of grouting parameters on the damage evolution of the composite structure is clarified. S5 Composite Structure Stability Determination: Based on mechanical parameters, the strength recovery coefficient of the composite structure is calculated. Combined with parameters from three dimensions—acoustic emission damage characteristics, microscopic deformation localization characteristics, and microscopic filling rate characteristics—the stability of the filling body-surrounding rock composite structure is quantitatively determined, and the optimal grouting reinforcement parameters for the target surrounding rock are determined.
2. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S1, the target surrounding rock is red sandstone, and the standard rock sample is a cylindrical standard sample with a diameter of φ50mm×100mm, and the height and diameter errors do not exceed ±0.3mm; the uniaxial compression test adopts displacement control and the loading rate is 0.03mm / min; the grouting material is a high-permeability nano-grouting material or 42.5P・O type ordinary silicate cement grouting material, wherein the maximum particle size of the high-permeability nano-grouting material is <10μm, the density is 3.77g / cm³, and the specific surface area is 421m² / kg.
3. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 2, characterized in that, In step S1, the grouting pressure range of the high-pressure grouting is 2MPa~15MPa, and the water-cement ratio of the grouting material ranges from 0.5 to 0.9; the standard curing conditions are a temperature of 20℃ and a relative humidity of 90%RH.
4. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S2, the parameters of the acoustic emission monitoring module are set as follows: trigger threshold 45dB, sampling frequency 1MHz, preamplifier gain 40dB, and high vacuum grease is used as a coupling agent to fix the acoustic emission sensor to the sample surface; the three-dimensional full-field strain observation module is a three-dimensional digital image correlation binocular vision measurement system. Before the test, a matte white background with black speckle is made on the sample surface to complete the binocular camera calibration, and the calibration reprojection error is less than 0.02 pixels.
5. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S3, the uniaxial compression loading test uses displacement control with a loading rate of 0.03 mm / min; the longitudinal wave velocity is calculated using the following formula: in, Let L be the longitudinal wave velocity, and L be the distance between the wave emission point and the receiving point. The time it takes for a longitudinal wave to travel through the rock. This ensures zero delay for the instrument system.
6. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S3, the CT three-dimensional scan is used to reconstruct the three-dimensional structure of internal cracks and pores of the sample, and to distinguish the three phases of rock matrix, pores and slurry by threshold segmentation, and to quantitatively analyze porosity and crack filling rate; the SEM scan is used to observe the micromorphology of slurry-rock interface, the development characteristics of hydration products and the interface bonding state.
7. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S4, the crack initiation and propagation law analysis includes: characterizing the damage accumulation process based on acoustic emission ringing count and cumulative ringing count, distinguishing tensile cracks from shear cracks with AF=100RA as the dividing line, and statistically analyzing the proportion and evolution law of the two types of cracks, where RA is the ratio of acoustic emission signal rise time to amplitude, and AF is the ratio of acoustic emission signal ringing count to duration; the surface non-uniform deformation characteristic analysis includes: analyzing the evolution law of overall axial strain and radial strain of the sample based on three-dimensional full-field strain data, extracting the development process of strain localization zones, and quantifying the strain difference inside and outside the localization zones.
8. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 1, characterized in that, In step S5, the strength recovery coefficient The calculation formula is: in, The peak compressive strength of the intact surrounding rock. The residual strength of the fractured surrounding rock. This represents the peak compressive strength of the infill-surrounding rock composite structure specimen.
9. The method for damage monitoring and stability determination of infill-surrounding rock composite structures based on multi-source information fusion according to claim 8, characterized in that, In step S5, the stability determination rule is as follows: the higher the strength recovery coefficient, the lower the cumulative ringing count of the pre-peak acoustic emission, the lower the degree of strain localization on the sample surface, and the higher the crack filling rate, the better the stability of the filling body-surrounding rock composite structure; the grouting parameters corresponding to the peak value of the strength recovery coefficient are taken as the optimal grouting reinforcement parameters for the target surrounding rock.
